Mining in Medieval Serbia - Fostikov, Aleksandra (Napredak, 2024)
Mining, also known as Montanindustrie, in the territory of medieval Serbia had a long road of development, from surface mining to dizzying achievements which began with the arrival of the Old Saxons in the 13th century. Thanks to their influence, or the combination of technological development and available raw materials, Serbia underwent a general economic rise and as early as the first half of the 15th century it accounted for the production of one quarter or one fifth of silver in Europe. However, the Old Saxon influence was not limited only to mining, but it also included the development of mining towns, as well as craft industry. That is why this paper elaborates on the development of mining in the territory of medieval Serbia from its settlement until its fall under the Ottoman rule, with the aim of exploring long-term processes which substantially affected the change not only in the economy, but in society as well.